Leader trustworthy behavior and organizational trust: the role of the immediate manager for cultivating trust. Issue 12 (10th August 2016) - Legood, Alison; Thomas, Geoff; Sacramento, Claudia
Abstract: Drawing from both trust‐building theory and interpersonal trust literature, we investigate how trust between a leader and follower may be leveraged to influence organizational trust. We also explore the mediating mechanisms of this link and test a potential moderator. A cross‐sectional, multifoci design was adopted and participants were 201 employees within a public sector organization. Leader trustworthy behavior was found to predict organizational trust, mediated by trustworthiness perceptions and trust in the leader. Support for the boundary condition was found; namely, when leaders were more senior, the relationship between trustworthy behavior and organizational trust was stronger. The findings suggest that leaders can meaningfully influence organizational trust perceptions through the enactment of trustworthy behavior, although the strength of this effect varied as a function of their position.